The Composition of Algae, Cyanobacteria and the Application in Water Quality Assessment in Truc Bach Lake, Hanoi - Dung, Nguyen Thi; Hung, Vu Duy; Lien, Nguyen Thuy; Ha, Le Thu; Dau, Pham Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Phytoplankton and water samples were repeatedly collected in November 2015; February and May 2016 from 12 sampling sites in Truc Bach lake. 115 species and subspecies of phytoplankton had been recorded. They belong to 5 divisions (Cyanobacteriophyta, Bacillariophyta, Pyrrophyta, Euglenophyta, Chlorophyta). Cyanobacteriophyta hadthe largest density (23 species, 8021 cells/l). Based on Palmer index (Pollution index), Shannon - Weiner index (Diversity index)and physiochemical and biological parameters, we found that Truc Bach lake was polluted with organic substances, especially substances that are hard to decompose and nitrogenous sewage. Keywords: Phytoplankton, biodiversity, water quality, Truc Bach lake.